Analisis Pencatatan dan Pengelolaan Arsip Untuk Mendukung Pelayanan Informasi Pada Sub Bagian Tata Usaha di Upt. Dinas Tanaman Pangan dan Hortikultura Provinsi Sumatera Utara - Azzahra Tri Najla S; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2024)
Archives are a collection of letters that are stored systematically and have the function of storing information which can later be used as accountability and valid legal evidence. Archives have an important role in the operational system of an organization or company. If a company has poor records management, it will difficult to find the information needed, thereby hampering further work processes. The discussion that will be discussed in this research is how to implement the recording and archive management system in the Administration sub-section at UPT. North Sumatra Province Food Crops and Horticulture Service. The research method that the author uses is qualitative research and uses descriptive data analysis by conducting direct observations for one month at UPT. North Sumatra Province Food Crops and Horticulture Service. The research results show that archive management at UPT. The Food Crops and Horticulture Department is not running optimally. This is due to the fact that archives have not been digitized so everything is still done manually.